FINANCIAL INTELLIGENCE OF SMALL ENTREPRENEURS IN MANAGING FINANCIALS - Yuli Yanti Wulan; Indrawati Yuhertiana (Universitas 17 Agustus 1945 Surabaya, 2021)
Micro, Small and Medium Enterprises have a significant contribution to the economy in Indonesia, but a phenomenon that often occurs is the problem of business actors who do not use financial reports in running their business but their business is still running, this study aims to find out how the financial intelligence of small entrepreneurs in managing finances his efforts.This research is a qualitative research, data collection techniques are carried out by observation, interviews, and documentation studies. Selection of informants using purposive sampling method based on the criteria that the informants are small entrepreneurs who have run their business for at least 5 years and do not make financial reports.The findings of this study indicate that the importance of financial intelligence in the financial management of micro, small and medium enterprises (MSMEs) is considered to be still poorly understood by entrepreneurs and still lacks understanding of financial reports. Small and medium entrepreneurs are still working on bookkeeping to the extent of recording income and expenses. As a result, the company's net income and income tax estimates are difficult to know. This becomes a difficulty for many small entrepreneurs to determine a business development strategy.